2016
DOI: 10.1136/heartjnl-2016-309706
|View full text |Cite
|
Sign up to set email alerts
|

Variation in hospital performance for heart failure management in the National Heart Failure Audit for England and Wales

Abstract: Objective: Investigation of variations in provider performance and its determinants may help inform strategies for improving patient outcomes. Methods:We used the National Heart Failure Audit comprising 68,772 patients with heart failure with reduced left ventricular ejection fraction (HFREF), admitted to 185 hospitals in England and Wales (2007-2013). We investigated hospital adherence to three recommended key performance measures (KPM) for in-hospital care (ACE-inhibitors or ARBs on discharge, beta-blockers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
1
17
3
Order By: Relevance
“…Quality of care for HF is publicly reported among the nation's hospitals and registries, such as the American Heart Association's Get With the Guidelines programme that provides feedback for process measures and outcomes to participating hospitals . Similar measures have been reported from the United Kingdom and other countries …”
supporting
confidence: 83%
“…Quality of care for HF is publicly reported among the nation's hospitals and registries, such as the American Heart Association's Get With the Guidelines programme that provides feedback for process measures and outcomes to participating hospitals . Similar measures have been reported from the United Kingdom and other countries …”
supporting
confidence: 83%
“…As suggested in an earlier report, interventions to tackle the low referral rates after discharge could also contribute to reductions in between-hospital variation in quality of care. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Emdin et al have previously examined the adherence to treatment guidelines for patients discharged from hospital following admission for HF using NHFA data. 8 As part of the current analysis, these data were reanalysed to establish the potential for improving uptake of ACEi, BBs and optimal therapy (one or both of ACEi and BBs if not contraindicated) for the years 2010–2013. Not all patients are clinically eligible to receive all these drugs as they may be contraindicated to one or more treatments.…”
Section: Methodsmentioning
confidence: 99%
“…7 The NHFA suggests that not all patients with HF are receiving treatment according to guidelines. 8 In particular, UK guidelines recommend that, following hospitalisation for HF, patients should receive ACE inhibitors (ACEi) and beta blockers (BB) as first-line therapy. 9 A recent study of the NHFA has shown that, while treatment with ACEi and BBs has been improving over time, many patients are still not receiving these therapies: in 2013, only 81.7% of patients who were eligible were receiving BBs and 83.7% were receiving ACEi.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation